The importance of cash flow statement in reducing credit risk and liquidity: بحث تطبيقي في مصرف الرشيد (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Banks face different types of banking risks that limit the performance of its functions and achieve its objectives, including the financial risk that is based on current research into two types including a credit and liquidity risks. And established credit risk due to the possibility of delaying the borrowers to fulfill their obligations to the bank when due or non-payments on according to the terms agreed upon, while liquidity risk arises as a result of the inability of the bank to fund the financial needs, any inability to provide cash to pay its obligations short on credit without achieving tangible loss or the inability to employ the funds properly and show the liquidity risk in the event of inadequate cash inflows to the bank for an interview cash outflows.The research problem is embodied in the weakness of interesting banks departments prepare a cash flow analysis, study, detect and ignore its importance in reducing or reduce the credit and liquidity risks. As decisions granting credit based on the study list of the general budget and profit and loss account of the borrower without studying cash flow analysis revealed, and the variability of cash flows from the financial department staff and management of credit in the bank disclosed, as well as the lack of flow from the presence of corporate borrowers when applying for detection loans as a result of the weakness of experience and knowledge in the preparation of cash flow from working in the corporate borrowers revealed.Was based search the premise that interest banks departments prepare revealed cash flow, study and analysis contributes to predict the deficit or surplus cash, which helps to reduce the credit and liquidity risk, the population comprised of government banks The research sample Rasheed Bank, was chosen years (2004 - 2006) as a border temporal to search for the availability of financial her menus, the latest lists of financial statements during the period of research writing, this came Find the recommendations and conclusions and it was the most important conclusion that the Rasheed Bank has not been adopted by the temporal limits of the search on qualitative analysis and application of modern technologies and research postgraduate students and he classifies liquidity and credit as directed CBI, the most important recommendation was doing research is the need to prepare a cash flow detection, according to the seventh international standard accounting and al-Qaida No. (7) and the instructions of the Central Bank of Iraq.